Physicochemical characterization of dual action liposomal formulations: anticancer and antimicrobial. Issue 8 (August 2019) - Das, Asmita; Konyak, Pangwan M.; Das, Argha; Dey, Subrata Kumar; Saha, Chabita
Abstract: Background: Cancer till date remains one of the world's most life threatening disease accompanied by risk of secondary infections. Therefore formulations carrying anticancer drugs which can also decrease the risk of secondary infection are inevitable. Chemotherapeutic drug doxorubicin along with flavonoids quercetin and epigallocatechin gallate (EGCG) is simultaneously loaded on liposomal formulation exploiting the amphiphilic property of the liposomes. Results: Atomic force microscope imaging reveal the size of liposomal formulation loaded with doxorubicin, quercetin and EGCG to be greater than void liposome confirming the presence of drugs. Liposomal stability is improved by PEGylation; adding to the drug release time in vitro . The charge of phosphatidylcholine is rendered positive by coating the formulation with histone. The average size of the formulation is 342 nm. The encapsulation efficiency of doxorubicin, quercetin and EGCG is found to be 65.8%, 96.8% and 98% respectively. The above formulation demonstrated both anticancer and antimicrobial activity. Conclusion: The formulation will provide dual anticancer and antimicrobial therapy thereby evading secondary infection in cancer patients along with chemotherapy.